Primary Nonfunction of Renal Allograft Secondary to Acute Oxalate Nephropathy - Ravi Parasuraman; Ping L. Zhang; Dilip Samarapungavan; Krishna Pothugunta; Gampala Reddy; Leslie Rocher; Francis Dumler; Vandad Raofi; Steven Cohn; Alan Koffron (Case Reports in Transplantation)
Primary nonfunction (PNF) accounts for 0.6 to 8% of renal allograft failure, and the focus on causes of PNF has changed from rejection to other causes. Calcium oxalate (CaOx) deposition is common in early allograft biopsies, and it contributes in moderate intensity to higher incidence of acute tubular necrosis and poor graft survival. A-49-year old male with ESRD secondary to polycystic kidney disease underwent extended criteria donor kidney transplantation. Posttransplant, patient developed delayed graft function (DGF), and the biopsy showed moderately intense CaOx deposition that persisted on subsequent biopsies for 16 weeks, eventually resulting in PNF. The serum oxalate level was 3 times more than normal at 85 μmol/L (normal <27 μmol/L). Allograft nephrectomy showed massive aggregates of CaOx crystal deposition in renal collecting system. In conclusion, acute oxalate nephropathy should be considered in the differential diagnosis of DGF since optimal management could change the outcome of the allograft.